Antimicrobial Activity of Extracts of Two Native Fruits of Chile: Arrayan (Luma apiculata) and Peumo (Cryptocarya alba) - Viktorová, Jitka; Kumar, Rohitesh; Řehořová, Kateřina; Hoang, Lan; Ruml, Tomas; Figueroa, Carlos R; Valdenegro, Monika; Fuentes, Lida (Antibiotics (Basel), 2020)
Arrayan and peumo fruits are commonly used in the traditional medicine of Chile. In this study, the concentration of the extracts halving the bacterial viability and biofilms formation and disruption of the drug-sensitive and drug-resistant strains of Staphylococcus aureus and Pseudomonas aeruginosa was determined. The chemical composition of extracts was analyzed by high-resolution liquid chromatography coupled with mass spectrometry (U-HPLC/MS). The arrayan extract (Inhibitory concentration IC50 0.35 ± 0.01 mg/mL) was more effective than peumo extract (IC50 0.53 ± 0.02 mg/mL) in the inhibition of S. aureus planktonic cells. Similarly, the arrayan extract was more effective in inhibiting the adhesion (S. aureus IC50 0.23 ± 0.02 mg/mL, P. aeruginosa IC50 0.29 ± 0.02 mg/mL) than peumo extracts (S. aureus IC50 0.47 ± 0.03 mg/mL, P. aeruginosa IC50 0.35 ± 0.01 mg/mL). Both extracts inhibited quorum sensing in a concentration-dependent manner, and the most significant was the autoinducer-2 type communication inhibition by arrayan extract. Both extracts also disrupted preformed biofilm of P. aeruginosa (arrayan IC50 0.56 ± 0.04 mg/mL, peumo IC50 0.59 ± 0.04 mg/mL). However, neither arrayan nor peumo extracts disrupted S. aureus mature biofilm. U-HPLC/MS showed that both fruit extracts mainly possessed quercetin compounds; the peumo fruit extract also contained phenolic acids and phenylpropanoids. Our results suggested that both extracts could be used as natural antimicrobials for some skin and nosocomial infections.